Use of Per-Operative Angiogram and Doppler Ultrasound as an Adjunct to Assess the Cerebral Vessels Following Aneurysmal Brain Surgery - Khan, Awais Ali; Habib Ullah Khan; Khurshid Ali Bangash; Shahzad Ahmed Qasmi; Syed Adeel Ahmed; Asif Hashmat; Babar Shamim (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the efficacy of per-operative angiogram and Doppler ultrasound as an adjunct to assess the cerebral vessels during intracranial aneurysm clipping surgery.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Neurosurgery, Combined Military Hospital, Rawalpindi Pakistan, from Jan 2020 to Dec 2021.Methodology: Forty-eight diagnosed cases of subarachnoid haemorrhage secondary to ruptured aneurysm were included. All the patients who were not coiled-able (broad-based, multi-lobed, complex) were operated on (craniotomy and clipping of aneurysm). Intraoperative angiogram and Doppler ultrasound of cerebral vasculature were done in all cases to see the patency of vessels and the position of clips.Results: Mean age of the patients was 43.97±8.23 years. 24(50.00%) patients had anterior communicating artery aneurysms, 18(37.50%) had middle cerebral artery aneurysms, whereas 6(12.50%) were of an anterior cerebral artery. Craniotomy and clipping of aneurysm were done in all the cases; among them, 15(31.25%) were operated on early (between 48-96 hrs), whereas 33(68.75%) were operated on after 10-14 days. Per-operatively, cerebral angiogram and Doppler ultrasound were used to assess the cerebral vasculature and position of the clip. About of 5(10.00%) required clip readjustment, 4(8.33%) had parent vessel occlusion, 10(20.83%) required vasodilator therapy due to vasospasm, and 4(8.33%) had residual aneurysm neck. All these were rectified during the same procedure.Conclusion: Per-operative angiography and Doppler ultrasound are useful adjuncts in aneurysmal brain surgery to prevent complications like cerebral ischemia, recurrence, residual aneurysm and re-bleed.